Isolation of starch and protein degrading strain Bacillus subtilis FYZ1-3 from tobacco waste and genomic analysis of its tolerance to nicotine and inhibition of fungal growth - Ye, Changwen; Liu, Dandan; Huang, Kuo; Li, Dong; Ma, Xinxin; Jin, Yiying; Xiong, Hanguo (Frontiers in Microbiology, 2023)
Aerobic fermentation is an effective technique for the large-scale processing of tobacco waste. However, the specificity of the structure and composition of tobacco-derived organic matter and the toxic alkaloids in the material make it currently difficult to directly use microbial agents. In this study, a functional strain FYZ1-3 was isolated and screened from thermophilic-phase samples of tobacco waste composting. This strain could withstand temperatures as high as 80 °C and grow normally at 0.6% nicotine content. Furthermore, it had a strong decomposition capacity of tobacco-derived starch and protein, with amylase activity of 122.3 U/mL and protease activity and 52.3 U/mL, respectively. To further understand the mechanism of the metabolic transformation of the target, whole genome sequencing was used and the secondary metabolite gene cluster was predicted. The inhibitory effect of the strain on common tobacco fungi was verified using the plate confrontation and agar column methods. The strain FYZ1-3 was Bacillus subtilis, with a genome size of 4.17 Mb and GC content of 43.68%; 4338 coding genes were predicted. The genome was annotated and analyzed using multiple databases to determine its ability to efficiently degrade starch proteins at the molecular level.Moreover, fourteen functional genes related to nicotine metabolism were identified, primarily located on the distinct genomic island of FYZ1-3, giving a speculation for its nicotine tolerance capability on the molecular mechanism.Moreover, fourteen functional genes related to nicotine metabolism were identified, primarily located on the distinct genomic island of FYZ1-3, giving a speculation for its nicotine tolerance capability on the molecular mechanism. By mining the secondary metabolite gene cluster prediction, we found potential synthetic bacteriocin, antimicrobial peptide, and other gene clusters on its chromosome, which may have certain antibacterial properties. Further experiments confirmed that the FYZ1-3 strain was a potent growth inhibitor of Penicillium chrysogenum, Aspergillus sydowii, A. fumigatus, and Talaromyces funiculosus. The creation and industrial use of the functional strains obtained in this study provide a theoretical basis for its industrial use, where it would be of great significance to improve the utilization rate of tobacco waste.